2008
DOI: 10.1371/journal.pone.0003089
|View full text |Cite
|
Sign up to set email alerts
|

Directly Observed Therapy and Improved Tuberculosis Treatment Outcomes in Thailand

Abstract: BackgroundThe World Health Organization (WHO) recommends that tuberculosis (TB) patients receive directly observed therapy (DOT). Randomized controlled trials have not consistently shown that this practice improves TB treatment success rates. In Thailand, one of 22 WHO-designated high burden TB countries, patients may have TB treatment observed by a health care worker (HCW), family member, or no one. We studied whether DOT improved TB treatment outcomes in a prospective, observational cohort.Methods and Findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 18 publications
4
33
1
Order By: Relevance
“…Chiang Rai has a severe epidemic of HIV-associated TB, but it is unclear why the death rate should be particularly high among HIV-uninfected patients in that province (Siriarayapon et al 2002). Not receiving directly observed therapy by a health care worker was of borderline significance as a risk factor for death, a finding consistent with a previous observational study in Thailand that documented a small, but significant, association between directly observed therapy and improved TB treatment outcomes (Anuwatnonthakate et al 2008). These issues and the finding that age is a strong risk factor for death highlights the greatest limitation of our study: the absence of sufficient detail about co-morbid conditions that might be strongly associated with death.…”
Section: Discussionsupporting
confidence: 78%
“…Chiang Rai has a severe epidemic of HIV-associated TB, but it is unclear why the death rate should be particularly high among HIV-uninfected patients in that province (Siriarayapon et al 2002). Not receiving directly observed therapy by a health care worker was of borderline significance as a risk factor for death, a finding consistent with a previous observational study in Thailand that documented a small, but significant, association between directly observed therapy and improved TB treatment outcomes (Anuwatnonthakate et al 2008). These issues and the finding that age is a strong risk factor for death highlights the greatest limitation of our study: the absence of sufficient detail about co-morbid conditions that might be strongly associated with death.…”
Section: Discussionsupporting
confidence: 78%
“…DOT mandatory for noncompliant or at-risk patientsMonthly review, random urine testing and pill counts: all received FDC[28]Southern Thailand (1999)Rural/urban2HRZE 7 /4HR 7 ; 2HRZE 3 /4HR 3 4114New, smear positiveDOT supervisors not stated; various levels of DOT examined. Strict DOT referred to observers actually watching patients swallow all the drugs during the first 2 moNot strict DOT, referred to as SAT[29]San Francisco, USA (1998–2000)Urban2HRZE 3 /4HR 3 3723Culture positiveHCW at clinic, home, or workplace; enablers given: DOT mandatory for at-risk patients and noncomplianceMonthly review[30]Bangkok, Thailand (2004–2005)Urban2HRZE 7 /4HR 7 12564New, smear positiveCenter-based (HCW), family-based (FM), or hybrids of center/SAT based; or center + family DOTPatients who could not attend to be accommodated in center- or family based DOT, were assigned SAT[31]Thailand (2004–2006)Rural/urban2HRZE 7 /4HR 7 ; Other8031 (only 7070 analyzed for end-of- treatment analysis)4New, smear positive, drug susceptibleHCW observed ingest antituberculosis drugs at least 5×/week, trained FM observed patient ingest antituberculosis and record eventSelf-administered antituberculosis, reviewed monthly.Study [35] reported that 83 (7%) of the 1203 patients assigned to interventions were lost to follow-up, ie, defaulted; however, these defaulters were not reported according to their assigned interventions. Thus, this study was not included in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…The debate has continued, with some even advocating for a shift of resources away from DOT programmes (Barbara 2013; Gross 2009; Moonan 2011; Pasipanodya 2013). There are also debates as to the best delivery of DOT, for example, should it be through healthcare workers or family members (Anuwatnonthakate 2008; Dick 2005).…”
Section: Introductionmentioning
confidence: 99%